Perancangan Model Sistem Analisis Kinerja Keuangan Perusahaan (Pendekatan Sistem Dinamik) - Emir Yulfan (JURNAL TEKNIK INDUSTRI, 2011)
In a company, financial performance is important to be measured and evaluated to serve as the basis for decision making. Because of the financial system in the real world has a fairly high level of complexity, it takes a model as an abstraction of the real system. In this study would be designed model performance evaluation system of corporate finance and policy analysis using the methodology of Dynamic Systems. The results of the design of this model in the form of flow diagrams and mathematical equations folder, which can be used as a learning tool for simulation and enables users to learn a model of financial systems and analysis, and simulate the decisions made in financial problems and see how the effects of these decisions on financial performance. However, this model still requires validation, the reformulation model, and further development for example by adding other subsector than financial, which is closer to the real system.